Peran KKN UPN “Veteran” Jawa Timur Dalam Mengatasi Dampak Pandemi Covid-19 Terhadap Sektor Ekonomi, Pendidikan, dan Pariwisata - Felixtha Hernanda; Muhammad Ahsanul Hakam; Rizal Arifbillah; Taufikurrahman Taufikurrahman (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Ampel, a religious tourism destination, has been affected by the Covid-19 pandemic. Covid-19 is a virus by SARS-CoV-2. Therefore, there is an impact on society. In particular, the need to meet and carry out activities in public places. Based on data from the Java Post, visitors to the Sunan Ampel Tomb have decreased by 90 percent, this occurs in the Sunan Ampel area which is only applied to a maximum of 50 percent of the available capacity. The object of activities is carried out in the environment around Ampel religious tourism. This activities uses observation, literature references and recovery program planning which is carried out offline and online. So, according to the hypothesis, the Covid-19 pandemic has had a major impact on the economic, education and tourism sectors, such as receiving unequal and inappropriate social assistance, the difficulty of accepting distance learning (PJJ), the provision of internet quotas that cannot be maximized, and the decreased enthusiasm of the community to travel to tourist attractions. In the end, it is hoped that the KKN program for the 41 Ampel sub-district groups which is carried out online and offline can help community activities to live healthier during the pandemic.